Moth flies (Diptera, Psychodidae) living in the dark of caves in the Dinaric Karst - Wagner, Rüdiger; Rada, Tonći (Zootaxa, 2020)
Seoda cavernicola sp. nov. and Psychoda glamocensis sp. nov., are new species and cave dwellers from Bosnia and Hercegovina, and Croatia. Adults of S. cavernicola are pale and small; the eye bridge is reduced, ommatidia irregularly arranged, epandrium with a pair of setose excrescences. The eye bridge of P. glamocensis is likewise reduced with 2 or 3 irregularly ordered facet rows, palpus segments of some individuals are malformed; its closest relative is Psychoda alticola Vaillant based on the morphology of male and female genitalia as well as on COI barcodes.